Evaluasi Performa Teknologi Isolasi Dasar Tipe HDRB Pada Gedung Tidak Beraturan di Kawasan Gempa Tinggi - Cahyono, Achmad Rudy; Suswanto, Budi (Jurnal Aplikasi Teknik Sipil, 2024)
Earthquakes frequently occur in Indonesia, including in Cemagi, Bali, which has a high seismic activity level (PGA: 0.4275 g). This study aims to evaluate the performance of the High Damping Rubber Bearing (HDRB) base isolation technology in an apartment building in Cemagi, Bali, with a complex design and irregular concrete structure. The building consists of 1 basement floor and 5 apartment floors with varying floor heights. The structural performance evaluation is conducted based on ATC-40 guidelines and SNI 1727:2020, SNI 2847:2019, SNI 1729:2020, SNI 1726:2019 regulations. This research investigates the application of HDRB through pushover and time history analysis, considering various design factors and local seismic conditions. The results show that the use of HDRB with a diameter of 1 meter on exterior columns and 0.8 meters on interior columns reduces displacement by up to 63.55%.